Le langage, la pensée et les objets du monde - Perrine Marthelot (Methodos, 2014)
This paper analyses the evolution of the concept of meaning in the work of Karl Bühler, through the prism of the concept of « sphere », which was first developed by the German psychologists of the Würzburg school of experimental psychology (whom Bühler was a member). In 1907, Bühler uses this concept of sphere in correlation with the concept of intention (meinen) in order to build an alternative to the definition of meaning as an association of representations (Vorstellung). The first part of the present paper analyses the consequences of this articulation between meaning and intention, and those of the determination of the object of meaning in terms of this concept of sphere. But, though Bühler uses the concept of intention as a way to prove that meaning is a matter of thought (or knowledge), and that it is not based on representations, intention does not define by itself the essence of meaning, which is realised in the instrumental model of the three functions of language (discussed in the second part of the paper, from the point of view of the emergence of the function of Darstellung as the introduction of a third term in the relation of communication : the one of the world through the objects and the state of affairs). Given these two dimensions of the analyse of meaning, it is interesting to notice that Bühler uses the very same concept of sphere in the third part of his Theory of language, where it plays the role of a material clue, guiding the thought to the meaning through the consideration of a certain kind of factual knowledge (or knowledge of some properties of the things, grouped into spheres). The third part of the paper deals with the consequences of this new use of the concept of sphere for the definition of meaning – in the Theory of language.